Comparison between a genetic risk score and the European SCORE in cardiovascular events prediction in a primary prevention population. (14th October 2021) - Soares, C; Temtem, M; Mendonca, M I; Sousa, J A; Santos, M; Sousa, A C; Rodrigues, M; Henriques, E; Freitas, S; Borges, S; Guerra, G; Drumond, A; et al.
Abstract: Background: The risk for Coronary Artery Disease (CAD) can be estimated using different scores, such as the European SCORE (Systematic Coronary Risk Evaluation) scale or genetic risk score (GRS). The addition of GRS to the European SCORE may increase the precision of predicting MACE (Major Adverse Cardiovascular Events). Purpose: This study aims to compare the European SCORE and the multiplicative genetic risk score (mGRS) in predicting MACE. Methods and results: The study included 1110 asymptomatic individuals without known CAD from GENEMACOR prospective registry. We defined the primary endpoint of all-cause cardiovascular events. The study population had mean age of 51.6 years, 74.1% male and had risk factors of diabetes (11.6%), dyslipidemia (67.5%), hypertension (48.1%) and smoking (22.9%). Using C-index methodology, mGRS score was superior to SCORE in predicting MACE (mGRS = 0.832 Vs SCORE = 0.615; p=0.014). Conclusions: The mGRS score was superior to SCORE in predicting MACE in an asymptomatic and free of CAD population. Genetic information may improve cardiovascular risk stratification in primary prevention. FUNDunding Acknowledgement: Type of funding sources: None.